Electron beam formation in magnetron guns with cathodes of millimeter diameters: experiment and simulation - Mazmanishvili, O.S.; Reshetnyak, M.G.; Chertischev, I.A. (Problems of Atomic Science and Technology, 2023)
The characteristics of the electron beam generated by the magnetron gun are studied. The experiments were carried out with magnetron guns with secondary emission cathodes (cathode diameter 2 and 3 mm, anode diameter 15 and 50 mm) at the cathode voltage of 8…50 kV. The magnetic fields were created both by the solenoid and jointly by the solenoid and the permanent magnet. The possibility of controlling the beam diameter by varying the magnetic field is shown. Beam imprints were obtained on targets located at selected distances. The dependence of the transverse dimensions of the beam on the configuration of the magnetic field in the electron beam transport channel is numerically studied. It is shown that the experimental data are consistent with the results of numerical simulation.